(untitled) (Multidisciplinary Journal of Science and Technology, 2024)
In this article, the views of foreign and local scientists about the content and essence of the skill of critical thinking are detailed. Factors of formation of critical thinking skills in future teachers, aspects of knowledge and learning activities related to critical thinking skills are explained.